Photoshop Scalability: Keeping It Simple. - Cole, Clem; William, Russell (Communications of the ACM, 2010)
The article presents a case study in the form of a discussion by computer scientists Russell Williams and Clem Cole, who analyze software development challenges involving parallel computing, using examples from the Adobe Photoshop software application. Williams is Adobe's principal computer scientist for Photoshop, and Cole develops computer architecture for Intel. They address topics such as synchronization, scaling, and debugging in the context of parallel computing for digital image processing.